Effect of modified value added intellectual coefficient (VAIC) on performance & market value of Malaysian companies - Farah Ilyani binti Mohd Fadzlah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
This study examines the relationship between intellectual capital and traditional performance of companies in four sectors listed in Bursa Malaysia for the year 2008. The four sectors consist of consumer product, industrial product, technology and trading / services. The relationship is first examined between two dependent variables which are profitability and market value with efficiency of Value Added Intellectual Coefficient (VAIC) measured by three components of a company's relational capital, human capital and structural capital. This study also extends the study on current VAIC and modifies it with the addition of Research and Development (R&D) paradigm as proxy for innovation capital. The relationship is further examined between dependent variables and efficiency of MVAIC which measured by three components of VAIC with additional modification of innovation capital. The analysis indicates that the relationship between dependent and independent variables are varied. Company's IC efficiency can explain profitability but not market value. This study found that the relationships between dependent variables with RDE are negative but not significant, thus additional robustness tests are carried out and supported the expectations that companies which incur R&D expenditure have lower current income and expected to have a higher future income. This study might be useful to management of companies in understanding the components of IC and strive for main IC components in order to compete in knowledge based economy. The results have also documented that the level of capitalised R&D among companies in the industries is small and limited. Thus, the regulators should undertake proactive actions to encourage greater R&D activities among companies.